ANALISA KEMAMPUAN KERJA PEGAWAI KANTOR URUSAN AGAMA PADA PELAYANAN PENCATATAN NIKAH DI KECAMATAN KENDIT KABUPATEN SITUBONDO - Hasan Muchtar Fauzi; Andi Prayitno (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Abdurachman Saleh Situbondo, 2017)
This study aims to analyze the work ability of the employees of the religious affairs office (KUA) in providing marriage registration services to communities in the Kendit sub-district of Situbondo district. This research is a field research that uses a qualitative approach. Data analysis was performed to answer the research problems used descriptive analysis of the data derived from the results of interviews, questionnaires and the results of observations (observations). The results of the study show that the procedures at the Office of Religious Affairs (KUA) are quite good, but only lack of clear information to the community and the attitude of employees who are less responsive and not friendly to the public